Action of granulocyte-macrophage colony-stimulating factors: studies using a human leukemia cell line. - Lusis, A J (1980)
Granulocyte-macrophage colony-stimulating factors (CSFs) have previously been shown to stimulate colony formation in soft agar culture by a human myelogenous leukemia cell line known as KG-1. We have used KG-1 cells as a model system to investigate the interaction of CSF with myeloid cells. We now report that exposure of KG-1 cells to human CSFs in liquid culture results in a rapid (within 3 hr) burst of RNA synthesis and, after a lag of about 10 hr, a stimulation of DNA and protein synthesis. RNA and protein synthesis were maximally stimulated about 2-fold and DNA synthesis was stimulated about 2.5-fold. The stimulation was specific; various growth factors, hormones, and mouse CSFs had no effect on KG-1 macromolecular synthesis. Treatment with CSF did not discernibly alter the morphological appearance of the KG-1 cells (primarily myeloblasts) nor did it qualitatively affect the pattern of newly synthesized proteins separable by one- and two-dimensional electrophoresis. Several myeloid leukemia cell lines that were not responsive to CSF in agar culture, including a dedifferentiated variant of KG-1, showed little or no stimulation of macromolecular synthesis upon exposure to CSF. We have used the CSF-dependent stimulation of macromolecular synthesis of KG-1 to develop a rapid, sensitive microassay for human CSFs. The assay, involving thymidine incorporation by the cells, should be useful for characterization and purification of human CSFs.